Emerging Technologies for Real-Time Diffusion Performance. - Johnson, Bridget (Leonardo Music Journal, 2014)
With the ascendance of the field of new interfaces for musical expression, a new phase of sound diffusion has emerged. Rapid development is taking place across the field, with a focus on gestural interaction and the development of custom performance interfaces. This article discusses how composers and performers embracing technology have broadened the boundaries of spatial performance. A particular focus is placed on performance interfaces built by the author that afford the artist more control over performative gestures. These new works serve as examples of the burgeoning field of diffusion performance interface design.